Preparation, characterization, and pharmacokinetics of rivaroxaban cocrystals with enhanced in vitro and in vivo properties in beagle dogs - Meng, Yuanyuan; Tan, Fangyun; Yao, Jiaxin; Cui, Yanan; Feng, Yumiao; Li, Zhiping; Wang, Yuli; Yang, Yang; Gong, Wei; Yang, Meiyan; Kong, Xiaolong; Gao, Chunsheng (International journal of pharmaceutics: X, 2022)
Rivaroxaban (RIV) is a direct Factor Xa inhibitor anticoagulant, but the oral bioavailability of RIV is estimated to be only 60% due to its poor solubility. The aim of the present study was to improve the solubility and bioavailability of RIV. Five cocrystals—p-hydroxybenzoic acid (HBA), 2,4-dihydroxybenzoic acid (DBA), nicotinamide (NA), isonicotinamide (IA), and succinic acid (SA)—were used as cofomers and were successfully obtained and characterized by powder X-ray diffraction, thermal analysis, and Fourier transform infrared spectra. RIV-DBA and RIV-HBA cocrystals showed obvious improvements in solubility, dissolution (under sink conditions), and intrinsic dissolution rates versus RIV. Moreover, the dissolution of RIV-HBA, RIV-DBA, and RIV-SA cocrystals under non-sink conditions showed obvious “spring and parachute” patterns. The in vitro permeability levels in a Caco-2 cell model of RIV-DBA and RIV-IA cocrystals were significantly improved versus RIV. Pharmacokinetic studies in beagle dogs showed that RIV-DBA and RIV-HBA cocrystals had higher bioavailability than RIV. The enhancements in solubility and bioavailability indicate the potential of RIV cocrystals as a better candidate for the treatment of thrombosis versus RIV. [Display omitted]